Aplikasi Website Layanan Manajemen Sewa Rumah Tinggal - Kusumawati, Kiki; Intan Yulianawati (Jurnal Manajemen Informatika JAMIKA, 2026)
The number of migrants seeking their fortune in Jakarta remains high, according to information from the DKI Jakarta Population and Civil Registry Office in 2025, which recorded a decline in the number of migrants entering the Jakarta area. In addition to work, migrant workers also need decent and affordable housing that is within commuting distance of their workplace and affordable in terms of rent. Information and services regarding the availability of rental houses or apartments are crucial for workers or their families to find suitable and affordable housing. The purpose of this application is to provide information and facilitate transactions for renting apartments according to users' needs, managed by the apartment owners. To design an application, a method must be applied, namely the prototype method for developing a rental management website application system, with a database design that applies Unified Modeling Language (UML). The output of the rental management service website application is in line with the needs of rental management service users. Through testing using User Acceptance Testing (UAT), 81% of respondents stated that the application provided adequately meets the needs of landlords and tenants as users of the application.